EurAsian Matters: China, Europe, and the Transcultural Object, 1600-1800 - Grasskamp, Anna; Juneja, Monica (Transcultural Research – Heidelberg Studies on Asia and Europe in a Global Context, 2018)
The volume examines the mutually constitutive relationship between the materiality of objects and their aesthetic meanings. Its approach connects material culture with art history, curation, technologies and practices of making. A central dimension of the case studies collected here is the mobility of objects between Europe and China and the transformations that unfold as a result of their transcultural lives. Many of the objects studied here are relatively unknown or understudied. The stories they recount suggest new ways of thinking about space, cultural geographies and the complex and often contradictory association of power and culture. These studies of transcultural objects can suggest pathways for museum experts by uncovering the multi-layered identities and temporalities of objects that can no longer be labelled as located in single regions. It is also addressed to students of art history, of European and Chinese studies and scholars of consumer culture. « This eagerly awaited volume offers deep and extensive insights into the fast-growing field of material culture studies. Its fresh approach to Eurasian objects and materialities will serve as useful reading for all scholars interested in transcultural and global studies. A very helpful introductory essay. » Sabine du Crest, University of Bordeaux Montaigne, Former Fellow, The Harvard University Center for Italian Renaissance Studies